Frequency of Vitamin D Deficiency in Children with Tuberculosis - Saima Rayaz, Attaullah Bizenjo, Mohammad Hussain, Mohammad Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the frequency of vitamin d deficiency in children with tuberculosis. Study Design: Case control study Place and Duration of Study: Department of Pediatric Medicine Unit 2, Sandeman Provincial Hospital, Quetta from 1st December 2021 to 31st May 2022. Methodology: One hundred children from 1 to 15 years which were divided into two groups. Group A had 50 patients/children suffering from tuberculosis while Group B had 50 healthy controls. A 2cc blood was withdrawn for the vitamin D3 testing. The results and confounding factors for vitamin D deficiency were compared within both groups. Results: The mean age of the cases and controls was 7.5±2.3 and 4.2±1.2 years respectively. There were more boys in cases with vitamin D deficiency while higher number of girls was observed in the vitamin D deficient controls. The Vitamin D levels of children with tuberculosis were compared with the controls and it was observed that 34% cases with severe vitamin D deficiency and 32% with mild vitamin D deficiency where a significant variance of controls results was noticed with 20% and 24% cases of severe and mild vitamin D deficiency. Conclusion: The frequency of vitamin D deficiency in children with tuberculosis was 66% reported. Keywords: Frequency, Vitamin D deficiency, Children, Tuberculosis